Multisensory perception of the six basic emotions is modulated by attentional instruction and unattended modality - Takagi, Sachiko; Hiramatsu, Saori; Tabei, Ken-ichi; Tanaka, Akihiro (Frontiers in Integrative Neuroscience, 2015)
Previous studies have shown that the perception of facial and vocal affective expressions interacts with each other. Facial expressions usually dominate vocal expressions when we perceive the emotions of face-voice stimuli. In most of these studies, participants were instructed to pay attention to the face or voice. Few studies compared the perceived emotions with and without specific instructions regarding the modality to which attention should be directed. Also, these studies used combinations of the face and voice which expresses two opposing emotions, which limits the generalizability of the findings. The purpose of this study is to examine whether the emotion perception is modulated by instructions to pay attention to the face or voice using the six basic emotions. Also we examine the modality dominance between the face and voice for each emotion category. Before the experiment, we recorded faces and voices which expresses the six basic emotions and orthogonally combined these faces and voices. Consequently, the emotional valence of visual and auditory information was either congruent or incongruent. In the experiment, there were unisensory and multisensory sessions. The multisensory session was divided into three blocks according to whether an instruction was given to pay attention to a given modality (face attention, voice attention, and no instruction). Participants judged whether the speaker expressed happiness, sadness, anger, fear, disgust or surprise. Our results revealed that instructions to pay attention to one modality and congruency of the emotions between modalities modulated the modality dominance, and the modality dominance is differed for each emotion category. In particular, the modality dominance for anger changed according to each instruction. Analyses also revealed that the modality dominance suggested by the congruency effect can be explained in terms of the facilitation effect and the interference effect.